Faktor Dominan Penurunan Pertumbuhan Ekonomi Batam - Daris Purba; Asron Saputra (LPPM Universitas Putera Batam, 2018)
Economic development in Batam has been slowing down in recent years. Batam PDRB has shown downturn tren. Between 2015 and 2016 there were 110 companies closed operation with 53 others were closing their operations in the beginning of 2017. As the result of the condition, the central government changed all top officers of BP Batam in 2017. This reseach is set to find the dominant factors of the downturn of Batam economic growth. This research aim to find the dominant factors of the downturn using qualitative descriptive method with comparative analysis. The finding shows that the dominant factor of economic in Batam is from FDI. FDI in Batam has been reduced gradually since 2012 which led to macro economic downturn in Batam. This downturn of FDI is a result of these factors: (1) As a direct impact of global economic downturn as Batam lies its economic activity to global export-import; (2) Losing its competitive advantage by the lack of proper infrastructure and electricity for industrial need; (3) The rise of other FTZ in China and Malaysia; (4) The complicated licencing prosess from two governmental body – BP Batam and Pemko Batam; (5) The economic protection policy from government that put a high tariff for trading goods from Batam to the rest of Indonesia borders making investors have not benefited from their position in Batam to enter Indonesia market; (6) The rise of workers wage; that only ranked second after Jakarta.